Integrative multi‐omics analyses of date palm (Phoenix dactylifera) roots and leaves reveal how the halophyte land plant copes with sea water - Mueller, Heike M.; Franzisky, Bastian L.; Messerer, Maxim; Du, Baoguo; Lux, Thomas; White, Philip J.; Carpentier, Sebastien C.; Winkler, Jana Barbro; Schnitzler, Joerg‐Peter; El‐Serehy, Hamed A.; Al‐Rasheid, Khaled A. S.; Al‐Harbi, Naif; et al. (Wiley, 2024)
Date palm (Phoenix dactylifera L.) is able to grow and complete its life cycle while being rooted in highly saline soils. Which of the many well-known salt-tolerance strategies are combined to fine-tune this remarkable resilience is unknown. The precise location, whether in the shoot or the root, where these strategies are employed remains uncertain, leaving us unaware of how the various known salt-tolerance mechanisms are integrated to fine-tune this remarkable resilience. To address this shortcoming, we exposed date palm to a salt stress dose equivalent to seawater for up to 4 weeks and applied integrative multi-omics analyses followed by targeted metabolomics, hormone, and ion analyses. Integration of proteomic into transcriptomic data allowed a view beyond simple correlation, revealing a remarkably high degree of convergence between gene expression and protein abundance. This sheds a clear light on the acclimatization mechanisms employed, which depend on reprogramming of protein biosynthesis. For growth in highly saline habitats, date palm effectively combines various salt-tolerance mechanisms found in both halophytes and glycophytes: “avoidance” by efficient sodium and chloride exclusion at the roots, and “acclimation” by osmotic adjustment, reactive oxygen species scavenging in leaves, and remodeling of the ribosome-associated proteome in salt-exposed root cells. Combined efficiently as in P. dactylifera L., these sets of mechanisms seem to explain the palm's excellent salt stress tolerance.